Flexibility and competitiveness: Labour market flexibility, innovation and organisational performance. Finnish national report - Rita Asplund (The Research Institute of the Finnish Economy (ETLA), 2003)
This overview report on flexibility and competitiveness for Finland starts with an outline of the performance and consequent restructuring of the Finnish economy over the past two decades. It then continues with a presentation and discussion of Finnish technology policy and the ICT miracle of the 1990s, which are key supporting factors behind the Finnish success story. The focus then shifts to an outline of the main features of labour market legislation and organisations, including the collective bargaining system implemented in Finnish working life, and the main modes of labour market flexibility. The report concludes with a summary of the main outcomes from interviews with representatives of the Ministry of Industry and Trade, the Ministry of Labour, the National Technology Agency (Tekes), the Confederation of Finnish Industry and Employers (TT) and the Central Organisation of Finnish Trade Unions (SAK). – Finland ; labour market flexibility ; labour market institutions ; technology policy – – Tämä Suomen talouden joustavuutta ja kilpailukykyä koskeva katsaus kuvaa ensin yleisesti taloudellista kehitystä ja siitä johtuvaa rakennemuutosta viimeisten kahden vuosikymmenen aikana. Katsauksessa siirrytään tämän jälkeen kuvailemaan suomalaista teknologiapolitiikkaa ja 1990-luvun ICT-ihmettä, jotka yhdessä vaikuttivat ratkaisevasti Suomen menestystarinaan. Seuraavaksi esitetään pääpiirteittäin työmarkkinalainsäädäntöä ja -instituutioita, mukaan lukien työelämää ohjaavaa sopimusjärjestelmää, sekä työmarkkinoiden joustavuuden päämuotoja. Katsauksen lopussa on yhteenveto eri vaikuttajatahojen edustajien kanssa tehdyissä haastatteluissa esiin tulleista ajatuksista ja näkökohdista. Haastateltavia tahoja olivat kauppa- ja teollisuusministeriö, työministeriö. Tekes, Teollisuuden ja Työantajain Keskusliitto (TT) sekä Suomen Ammattiliittojen Keskusjärjestö (SAK). – Suomi ; työmarkkinoiden joustavuus ; työmarkkinoiden instituutiot ; teknologiapolitiikka
Keywords: O52; 330; Arbeitsmarktflexibilisierung; Arbeitsmarktpolitik; Forschungs- und Technologiepolitik; Finnland